Glory in their spirit : how four black women took on the Army during World War II - Bolzenius, Sandra M., 1959- (Women, gender, and sexuality in American history., 2018)
"In 1945, four African American female privates who were members of the Women's Army Corps (WAC) participated in a strike at Fort Devens, Massachusetts, and opted to take a court martial rather than accept discriminatory work assignments. As the army prepared for the court-martial and civil rights activists investigated the circumstances, competing commentaries in African American and mainstream newspapers ignited a passionate public response across the country. Indeed, the insurrection, now little remembered, became the most publicized and recorded protest of Black WACs during World War II as story of how four African American women pushed the army's segregation system to its breaking point. Drawing on relevant scholarship, archival work, newspaper responses to the strike, and interviews with the strikers or their families, Sandra Bolzenius shows how the strike at Ft. Devens demonstrates that army regulations prioritized white men, segregated African Americans, highlighted white women's femininity, and overlooked the presence of African American women. In drawing attention to these issues, this book is able to shed light on the experiences and agency of World War II Black WACs who resisted racial discrimination and asserted their entitlements as female military personnel, analyze military policies and their effects on Army personnel, particularly Black WACs, and investigate the Army's determination to maintain the existing social order through the strict segmentation of its troops based on race, gender, and rank."--Provided by publisher.